The Role of Financial Literacy and Entrepreneurial Orientation on MSME Sustainability: The Mediating Effect of E-Commerce - Endang Kristiawati; Giriati; Wendy; Helma Malini (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2024)
MSMEs play an important role, but there are still many problems to improve their performance. The effect of financial literacy and entrepreneurial orientation on general performance is the purpose of this study. This research was conducted at MSMEs in Pontianak City and Singkawang City. The research method used is descriptive quantitative. Quantitative research is an attempt by a researcher to gain knowledge by providing data in the form of numbers which will then be used to analyze information. The data used in this research is primary data. The soil test results show that the significance value of the two-tailed test is 0.00 <0.05, so e-commerce can mediate the effect of financial literacy on MSME performance. The Sobel test results also show that the significance value of the two-tailed test is 0.00 <0.05, so e-commerce can mediate the effect of Entrepreneurial Orientation on MSME performance. Understanding financial literacy and the use of e-commerce will help MSMEs manage their finances and leverage business opportunities more effectively, as well as make it easier to access financial resources needed for business sustainability.